2018
DOI: 10.2215/cjn.00800118
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury among Hospitalized Children in China

Abstract: Background and objectives High-quality epidemiologic data on AKI in children are particularly lacking in developing countries. This study aimed to assess the epidemiology and clinical correlates of AKI among hospitalized children in China. Design, setting, participants, & measurements We performed a multicenter study, in a cohort of hospitalized children aged 1 month to 18 years, from 25 general and children's hospitals in China during 2013-2015. We obtained patient-level data from the electronic hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…The AWARE (Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology) study, which enrolled ICUs in 32 hospitals in Asia, Australia, Europe, and North America, showed that the overall incidence of AKI in 4683 critically ill children was 26.9%, and the incidence of severe AKI (KDIGO stage 2 or 3) was 11.6% [ 8 , 14 ]. Another multi-center study reported an incidence of AKI of 20% in the total 101,836 pediatric inpatients from 25 centers in China [ 15 ], where AKI occurred in 49.1% of children with respiratory failure. In our cohort, the incidence of AKI in pediatric patients with COVID-19 was 1.2% (3/238), much less common than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The AWARE (Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology) study, which enrolled ICUs in 32 hospitals in Asia, Australia, Europe, and North America, showed that the overall incidence of AKI in 4683 critically ill children was 26.9%, and the incidence of severe AKI (KDIGO stage 2 or 3) was 11.6% [ 8 , 14 ]. Another multi-center study reported an incidence of AKI of 20% in the total 101,836 pediatric inpatients from 25 centers in China [ 15 ], where AKI occurred in 49.1% of children with respiratory failure. In our cohort, the incidence of AKI in pediatric patients with COVID-19 was 1.2% (3/238), much less common than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study highlighted the fact that much AKI in adults is community acquired which cannot be addressed using most EHR-enabled prediction models. While this is true in adult populations, pediatric AKI tends to be hospital rather than community acquired (48,49). Thus, it is possible that pediatric populations will benefit more substantially from predictive models.…”
Section: Predicting Acute Kidney Injury Eventsmentioning
confidence: 99%
“…Previous studies on AKI have mostly focused on adult and adolescent patients [19][20][21], and the investigation and study to evaluate the acute kidney injury of infants after operation are relatively rare,complications, hospitalization expenses and other adverse consequences of AKI in hospitalized infants are no less than those of adults, and the physiological regulation function of infants's own organs is worse than that of adults, which often results in worse prognosis than adults [22,23]. For this reason, researchers have made appropriate improvements in the diagnosis and treatment of AKI in infants with congenital heart diseases compared with adults, and tried to find more sensitive and accurate markers to monitor the occurrence and development of AKI in infants [24,25].…”
Section: Introductionmentioning
confidence: 99%